2021
DOI: 10.1111/1365-2435.13948
|View full text |Cite
|
Sign up to set email alerts
|

Efficient light‐harvesting of mesophotic corals is facilitated by coral optical traits

Abstract: Scleractinian corals are the primary building blocks of coral reef ecosystems. The underlying success of corals as ecosystem engineers is mainly due to the complex interaction that takes place between the coral hosts and their endosymbiont microalgae (family: Symbiodiniaceae). The coral-algal symbiosis is driven by solar energy and acts as the biological engine fuelling the reef (Roth, 2014). Corals have adapted to capture and maximize light under various environmental conditions, and it has been suggested tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 85 publications
1
14
0
Order By: Relevance
“…Overall, samples from shallow depths exhibited a more rapid attenuation of light in the tissue and a greater ability to cope with excess light under high intensities, given that above the tissue surface the escaping flux (Φ) was enhanced by up to twofold higher from the incident irradiance (Fig. 5 ), thus supporting previous ecophysiological observations of light-adapted photosynthetic performance 31 , 33 . On the colony scale, Hoogenboom et al 41 found evidence of a strong reduction in energy available for coral growth under high-light levels and suggested that corals avoid the costs of excessive light exposure by means of altering colony morphology.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Overall, samples from shallow depths exhibited a more rapid attenuation of light in the tissue and a greater ability to cope with excess light under high intensities, given that above the tissue surface the escaping flux (Φ) was enhanced by up to twofold higher from the incident irradiance (Fig. 5 ), thus supporting previous ecophysiological observations of light-adapted photosynthetic performance 31 , 33 . On the colony scale, Hoogenboom et al 41 found evidence of a strong reduction in energy available for coral growth under high-light levels and suggested that corals avoid the costs of excessive light exposure by means of altering colony morphology.…”
Section: Discussionsupporting
confidence: 83%
“…Based on the results of the morphometric analyses and the optical data from Kramer et al (2022 31 ; Tables S1-3 ), we performed a total of 112 optical simulations (Figs. 5 and 6 ; Figs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations